Responsible Investment and Stock Market Shocks: Short-Term Insurance without Persistence - Jana Eisenkopf; Steffen Juranek; Uwe Walz (British Journal of Management, 2022)
We investigate the differential effect of the COVID-19 shock on the share prices of firms with different levels of ESG (environmental, social and governance) scores. Thereby, we analyse whether and to what extent higher ESG ratings provided insurance for investors in the stocks of those firms during this shock. We focus our analysis on the European market, in which ESG investment plays a particularly important role. Using a broad sample of listed firms, we provide mixed evidence. On the one hand, we show that immediately after the start of the shock, firms with a higher ESG score outperformed their peers. On the other hand, this effect faded less than 6 weeks later. Given the quick recovery of the market, our findings support the idea that ESG stocks provide limited insurance and act as a risk-mitigating device in severe crises.
Keywords: 650